Does distance to hospital affect emergency department presentations and hospital length of stay among chronic obstructive pulmonary disease patients?. Issue 3 (20th March 2022) - Rana, Rezwanul; Gow, Jeff; Moloney, Clint; King, Alex; Keijzers, Gerben; Beccaria, Gavin; Mullens, Amy
Abstract: Background: The primary goal of chronic obstructive pulmonary disease (COPD) management is to optimise a patient's functional status and quality of life. By encouraging effective patient self‐management within primary healthcare, unplanned and potentially avoidable COPD admissions to the emergency department (ED) can be avoided. Aim: The aim of this study is to examine whether distance to hospital influences the rate of ED presentation, hospital admission and hospital length of stay for COPD patients. Methods: The 2016 to 2018 resulted in a total of 5253 patient presentations with a primary medical diagnosis code of J44 (COPD). These were at the main hospitals of three Queensland Hospital and Health Services: Toowoomba, Ipswich and Gold Coast. To examine the variations in patient characteristics based on distance, a one‐way ANOVA (analysis of variance) test was conducted. The Kruskal‐Wallis test indicated that there were group differences. Results: This study identified significant variation in COPD‐related hospital length of stay and distance to hospital among COPD patients within three hospitals in South East Queensland, Australia. These results confirm that distance plays an important role in determining duration of hospital stay (in number of days) among COPD patients, with clear evidence of the distance 'decay phenomenon'. It appears from the findings of the current study that distance to the hospital is not associated with the greater likelihood of ED presentation but may influence length of stay. Conclusions: Several distance‐specific studies have concluded that lower utilisation of hospital care is associated with distance to hospital.